Optimization Of Process Parameter On Friction Stir Welding Of Aluminium 6061 Using Partial Fraction Method - Mohd Amin, Azriszul; Sofree, Muhamad Syauqi (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Friction Stir Welding is a technique resulting in the material to produce a low distortion and high joint strength compared toother joining techniques. In this paper, we will be conducting Friction Stir Welding on Aluminium 6061 using mild steel. As there are less research were made to obtain the optimum parameter to conduct this technique, we will be searching for the optimum parameters on Friction Stir Welding. To determine the optimum process parameters, we will be setting parameters on the diameter of cylindrical tool pin, rotational speed of tools and the traverse speed of the tool tip. Generating MINITAB software on partial fraction will yield analysis on contour plot, surface plots for optimizations and the response optimization data for the parameters. Based on the findings, we are able to determine the optimum parameter for friction stir welding based on the set parameter. A brief discussion on the defects that occurred when conducting friction stir welding has also been presented.